Knowledge networks and tourism - McLeod, Michelle T. (ed.) (Routledge advances in tourism, 2015)
"The receipt of knowledge is a key ingredient by which the tourism sector can adjust and adapt to its dynamic environment. However although its importance has long been recognised the fragmentation within the sector, largely as a result of it being comprised of small and medium sized businesses, makes understanding knowledge management challenging. This book applies knowledge management and social network theories to the business of tourism to shed light on successful operations of tourism knowledge networks. It contributes specifically to understanding a network perspective of the tourism sector, the information needs of tourism businesses, social network dynamics of tourism business operation, knowledge flows within the tourism sector and the transformation of the tourism sector through knowledge networks. Social Network Analysis is applied throughout to fully explore the growth and maintenance of tourism knowledge networks and the relationships between tourism sector stakeholders in relation to their knowledge requirements. Knowledge Networks and Tourism will be valuable reading for all those interested in successful operations of tourism knowledge networks"--